Pelatihan Penyusunan Laporan Keuangan Berbasis Digital Pada Usaha Umkm Pabrik Kerupuk Dua Putra Bengkulu - Hidayah, Nenden Restu; Galung, Mia Margareta Huta (Universitas Dehasen Bengkulu, 2023)
Micro, Small and Medium Enterprises (MSMEs) have a very important role in the economy of a country. In Indonesia, MSMEs are the backbone of the economy with a significant contribution to economic growth, job creation and poverty alleviation. The Bengkulu Dua Putra Kerupuk Factory is an MSME engaged in the production and sale of crackers. This factory has the need to compile accurate financial reports and the training activity